Sharia stock performance of public listed companies on Bursa Malaysia / Mukhtar Samin - Samin, Mukhtar (2018)
The purpose of research is to see of sharia stock performance and the relationship of the financial ratio and the stock return that will be known as the performance. The performance we be defined using six ratio that is commonly us as the fundamental analysis in the market. The ratio are earnings per share (EPS), price earnings ratio (PER), net profit margin (NPM), return on equity (ROE), price to book value (PBV) and debt equity ratio (DER). From this ratio that will be collected from bursa Malaysia and only 30 sharia stock will be randomly pick as a sample from three sector that is consumer, technology and industrial sector. The data will be used is from 2014 until 2017 because at this time the sharia index are increasing so it is suitable to conduct the research at those time.